Big data help to define climate change challenges for the typical Mediterranean species Cistus ladanifer L. - Almeida, Alice Maria; Ribeiro, Maria Margarida; Ferreira, Miguel R.; Roque, Natália; Quintela-Sabarís, Celestino; Fernandez, Paulo (Frontiers in Ecology and Evolution, 2023)
Climate change’s huge impact on Mediterranean species' habitat suitability and spatial and temporal distribution in the coming decades is expected. The present work aimed to reconstruct rockrose (Cistus ladanifer L.) historical and future spatial distribution, a typically Mediterranean species with abundant occurrence in North Africa, the Iberian Peninsula, and Southern France. The R ensemble modeling approach was made using the biomod2 package to assess changes in the spatial distribution of the species in the Last Interglacial (LIG), the Last Glacial Maximum (LGM), and the Middle Holocene (MH), in the present, and in the future (for the years 2050 and 2070), considering two Representative Concentration Pathways (RCP 4.5 and RCP 8.5). The current species potential distribution was modeled using 2,833 occurrences, six bioclimatic variables, and four algorithms, Generalized Linear Model (GLM), MaxEnt, Multivariate Adaptive Regression Splines (MARS), and Artificial Neural Networks (ANN). Two global climate models (GCMs), CCSM4 and MRI-CGCM3, were used to forecast past and future suitability. The potential area of occurrence of the species is equal to 15.8% and 14.1% of the study area for current and LIG conditions, while it decreased to 3.8% in the LGM. The species’ presence diminished more than half in the RCP 4.5 (to 6.8% in 2050 and 7% in 2070), and a to low figure (2.2%) in the worst case scenario (RCP 8.5) for 2070. The results suggested that the current climatic conditions are the most suitable for the species' occurrence and that future changes in environmental conditions may lead to the loss of suitable habitats, especially in the worst-case scenario. The information unfolded by this study will help to understand future predictable desertification in the Mediterranean region and to help policymakers to implement possible measures for biodiversity maintenance and desertification avoidance.